The ganga paradox - Prica, Ines (Traditiones (Ljubljana), 2012)
The intention of this paper is to focus on the symbolic fate of an 'unusual' folklore expression which, thanks to is indisputable authenticity, has broken through to the status of internationally protected World Intangible Heritage while, at the same time, it has been stalked by the long-term and unsolved controversies of local political taboo and subversion.
Keywords: ethnology; Etnologija; folkloristics; Folkloristika; Politična folklora; Simboli; symbol; Croatia; Hrvaška; Hercegovina; ljudska glasba; folk music; ljudsko petje; ganga